The Pro-Choice Biblical Ethic of American Evangelical Scholars before the Religious Right - MacGregor, Kirk R. (Journal of Biblical literature, 2025)
Randall Balmer and Jonathan Dudley have documented that American evangelicals widely supported abortion before the rise of the Religious Right. In fact, Dudley has shown that, prior to Roe v. Wade, evangelicals worked to repeal state antiabortion laws that restricted legal abortions to those that saved the life of the mother. The most important of these efforts was a 1968 symposium of leading evangelical scholars cosponsored by Christianity Today and the Christian Medical Society. However, the reception of the Bible by the scholars at this symposium has heretofore not been analyzed. In this article, I argue that the so-called Protestant Symposium on the Control of Human Reproduction interpreted the Bible as supporting a moderate pro-choice ethic. With one exception, the participants viewed the scriptural data as compatible with either spirative soul-creationism or progressive traducianism. They held that, prior to birth, the conceptus is therefore not an actual person but a potential person, to be valued tremendously as a possible divine image-bearer but not more greatly than actual persons. The symposium concluded that biblical ethics sanction abortion when the mother's health is at risk, when the potential child's health is at risk, or when pregnancy results from rape or incest.